Differential effects of offspring and maternal inbreeding on egg laying and offspring performance in the burying beetle Nicrophorus vespilloides. (10th May 2018) - Ford, Lucy E.; Henderson, Kirsten J.; Smiseth, Per T.
Abstract: We investigate the effect of offspring and maternal inbreeding on maternal and offspring traits associated with early offspring fitness in the burying beetle Nicrophorus vespilloides . We conducted two experiments. In the first experiment, we manipulated maternal inbreeding only (keeping offspring outbred) by generating mothers that were outbred, moderately inbred or highly inbred. Meanwhile, in the second experiment, we manipulated offspring inbreeding only (keeping females outbred) by generating offspring that were outbred, moderately inbred or highly inbred. In both experiments, we monitored subsequent effects on breeding success (number of larvae), maternal traits (clutch size, delay until laying, laying skew, laying spread and egg size) and offspring traits (hatching success, larval survival, duration of larval development and average larval mass). Maternal inbreeding reduced breeding success, and this effect was mediated through lower hatching success and greater larval mortality. Furthermore, inbred mothers produced clutches where egg laying was less skewed towards the early part of laying than outbred females. This reduction in the skew in egg laying is beneficial for larval survival, suggesting that inbred females adjusted their laying patterns facultatively, thereby partially compensating for the detrimental effects of maternal inbreeding on offspring. Finally, we found evidence of a nonlinear effect of offspring inbreeding coefficient on number of larvae dispersing. Offspring inbreeding affected larval survival and larval development time but also unexpectedly affected maternal traits (clutch size and delay until laying), suggesting that females adjust clutch size and the delay until laying in response to being related to their mate.